2021
DOI: 10.1039/d1qo00822f
|View full text |Cite
|
Sign up to set email alerts
|

Extended enantiopure ortho-phenylene ethylene (o-OPE)-based helical systems as scaffolds for supramolecular architectures: a study of chiroptical response and its connection to the CISS effect

Abstract: A novel synthetic strategy based on a bifunctional stapled chiral nucleus from which segments of different lengths can be added to both ends of o-phenylene ethynylenes (o-OPEs) has been developed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 94 publications
7
17
1
Order By: Relevance
“…However, at the transitions with highest oscillator strength, the largest peaks of the ECD are generated at those wavelengths where UV-visible spectra have peaks (Figure S6) for different helices, both magnitudes are increasing with the pitch of the helices (Figure 3 and Supporting Information Table S2) for equidistant C−C bond helices at those wavelengths (again with the exception of the 2.50Åpitch).These results are similar as compared with real helices where the magnetic transition dipole moment (MTDM) increases with the turn of the helices reported in Ref. [68]. Interestingly, for the electric transition dipole moment, the increase happens exclusively in the component along the helix axis (Figure 4, top row).…”
Section: Transition Moments and Polarizabilitysupporting
confidence: 81%
See 1 more Smart Citation
“…However, at the transitions with highest oscillator strength, the largest peaks of the ECD are generated at those wavelengths where UV-visible spectra have peaks (Figure S6) for different helices, both magnitudes are increasing with the pitch of the helices (Figure 3 and Supporting Information Table S2) for equidistant C−C bond helices at those wavelengths (again with the exception of the 2.50Åpitch).These results are similar as compared with real helices where the magnetic transition dipole moment (MTDM) increases with the turn of the helices reported in Ref. [68]. Interestingly, for the electric transition dipole moment, the increase happens exclusively in the component along the helix axis (Figure 4, top row).…”
Section: Transition Moments and Polarizabilitysupporting
confidence: 81%
“…In addition, there are experimental reports pointing to a correlation between electronic circular dichroism (ECD) [62] and CISS [4,18,63,64,65,66,67,10,6]. In this context Mujica et al reported [68] that the transition magnetic dipole moment and its alignment with helix axis is important as it is directly related to the magnetic field involved in the CISS effect. Also, Fransson et al recently introduced a model where molecular polarizability was related to the polarization through its inclusion in the electron-phonon coupling term and related it to the optical activity [69].…”
Section: Introductionmentioning
confidence: 99%
“…This picture has been invoked to rationalize a connection between ECD and CISS based on the transition magnetic dipole moments in ECD by one of us. [68] Thus, to gain further insights into the observed pitch dependence of the ECD peaks, we analyze quantities accessible from the simulations. From our TDDFT calculations, it is evident that the magnitudes of the electric and magnetic transition dipole vectors m and m are changing randomly with the increase of the pitch of the helices for the first excited singlet state (Table S3).…”
Section: Transition Moments and Polarizabilitymentioning
confidence: 99%
“…[16] In addition, there are experimental reports pointing to a correlation between electronic circular dichroism (ECD) [62] and CISS. [4,6,10,18,[63][64][65][66][67] In this context Mujica et al reported [68] that the transition magnetic dipole moment and its alignment with helix axis is important as it is directly related to the magnetic field involved in the CISS effect. Also, Fransson et al recently introduced a model where molecular polarizability was related to the polarization through its inclusion in the electron-phonon coupling term and related it to the optical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the latter, Miguel, Longhi, and Cuerva 297 have reported a series of cyclophanes comprising a helical o -OPE foldamer and point chiral centers whose strong CPL emission can be turned off in the presence of Ag( i ) and switched on following the addition of acetonitrile. They also investigated the effect of the extension of the foldamer 298 and the derivatization of the point chiral centers on this scaffold, 299 yielding intense CPL emission, usually attaining | g lum | values around 1 × 10 −2 . It is essential to highlight that the inclusion of pyrene units attached to the point chiral centers of the cyclophane afforded a ratiometric probe based on CPL.…”
Section: Applicationsmentioning
confidence: 99%